1995
DOI: 10.1021/bi00045a039
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Liver Medium-Chain Acyl-CoA Dehydrogenase: Purification, Characterization, and the Mechanism of Interactions with Functionally Diverse C8-CoA Molecules

Abstract: We offer a large scale purification procedure for the recombinant human liver medium-chain acyl-CoA dehydrogenase (HMCAD). This procedure routinely yield 100-150 mg of homogeneous preparation of the enzyme from 80 L of the Escherichia coli host cells. A comparative investigation of kinetic properties of the human liver and pig kidney enzymes revealed that, except for a few minor differences, both of these enzymes are nearly identical. We undertook detailed kinetic and thermodynamic investigations for the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
89
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(108 citation statements)
references
References 18 publications
18
89
1
Order By: Relevance
“…Both enzymes show a similar chain length dependent decrease in the pK app going from 4-thia-C8 to 4-thia-C13 (Table 1; 9). Thus, these data are consistent with the close enzymological and structural similarities between these medium-chain enzymes (7,22,33,37; this work). Scheme 3 FIGURE 1: pH dependence of the polarization of 4-thia-trans-2-dodecenoyl-CoA bound to human wild-type medium-chain acylCoA dehydrogenase.…”
Section: -Thia-trans-2-enoyl-coa Analogues: Active Site Probessupporting
confidence: 84%
See 1 more Smart Citation
“…Both enzymes show a similar chain length dependent decrease in the pK app going from 4-thia-C8 to 4-thia-C13 (Table 1; 9). Thus, these data are consistent with the close enzymological and structural similarities between these medium-chain enzymes (7,22,33,37; this work). Scheme 3 FIGURE 1: pH dependence of the polarization of 4-thia-trans-2-dodecenoyl-CoA bound to human wild-type medium-chain acylCoA dehydrogenase.…”
Section: -Thia-trans-2-enoyl-coa Analogues: Active Site Probessupporting
confidence: 84%
“…Since all prior work with the 4-thia-enoyl-CoA ligands was done with enzyme isolated from pig kidney, and because of the minor differences in chain length specificity between the porcine and human enzymes (7,9,22,33,37), it was first necessary to repeat key control experiments with the recombinant human protein. Figure 1 shows a pH titration of the human wild-type medium-chain acyl-CoA dehydrogenase complexed with 0.87 equiv of 4-thia-trans-2-dodecenoyl-CoA.…”
Section: -Thia-trans-2-enoyl-coa Analogues: Active Site Probesmentioning
confidence: 99%
“…The dissociation constant determined by the BIAcore solution affinity assay of human wild type SBCAD with its product, tigyl-CoA, was 0.47 Ϯ 0.01 M, very close to its affinity for substrate (S)-2-methylbutyryl-CoA. This is also seen with other ACDs with their product (62).…”
Section: Surface Plasmon Resonance Analysis Of the Interactions Of Sbmentioning
confidence: 52%
“…It is notable that the overall K D values of V104L/F105L and F105L toward (S)-2-methybutyryl-CoA as measured with the BIAcore assay were higher than for wild type SBCADs, whereas the K D values of rat and human SBCADs toward (S)-2-methybutyryl-CoA were very close to each other (Table IV). Previous studies have shown that the reductive half-reaction is the rate-limiting step in the ACD dehydrogenation reaction (Scheme 1) when an acyl-CoA dehydrogenase reacts with its optimum substrate (61,62). Because both the V104L/ F105L and F105L mutants exhibit stabilization of the reduced flavin ring of FAD and increased catalytic rates for the overall reaction, the turnover rate for these two mutants of E ox S to I should remain at least as fast as in the wild type enzyme (Table II).…”
Section: Surface Plasmon Resonance Analysis Of the Interactions Of Sbmentioning
confidence: 99%
“…In recent years considerable effort has been put into the investigation of the mechanisms of these enzymes (Ghisla and Massey, 1989;Thorpe and Kim, 1995). Several ofthem have been cloned, expressed, and purified in their recombinant forms (Kieweg et al, 1997;Nandy et al, 1996;Peterson et al, 1995;Mohsen and Vockley, 1995), and the latter have been used extensively for biochemical studies also involving active site directed mutagenesis. While the differences in the primary sequence of recombinant MCADH's compared to those present in mitochondria might be restricted to the first amino acid(s) at the N-terminus, further post-translational changes may occur upon import into mitochondria.…”
Section: Introductionmentioning
confidence: 99%